A PORTRAIT OF HUMAN CULTURE TOWARD NATURE:AN ECOCRITICAL ANALYSIS OF THREE SHORT STORIESBY AKMAL NASERY BASRAL - Puji Pramesti, - (2008)
This paper, A Portrait of Human Culture toward Nature; An Ecocritical Analysis of Three Short Stories by Akmal Nasery Basral, deals with textual analysis on three short stories written by Akmal Nasery Basral, which is collected in an anthology entitled Ada Seseorang Dikepalaku yang Bukan Aku. This research is intended to find the role of physical setting and the environmental issues that are shown in the stories. There are two research questions the writer make to guide this research; (1) what role does the physical setting play in Dilarang Bercanda dengan Kenangan, Lebaran Penghabisan and Boyon? And (2) what environmental issues are shown in Dilarang Bercanda dengan Kenangan, Lebaran Penghabisan and Boyon? During the exploration to answer those questions, the writer conducted a deep analysis regarding characters and characterization, and setting, also, the environmental issues that occur in the stories. The research uses qualitative approach and descriptive method. The data, which are equipped with textual evidence, are collected by reading the short stories thoroughly and making a deep analysis of characters and characterization and setting, in the ecocritical point of view. This study found that the role of physical setting in the stories lie on the range of changing characterizations. It means that the setting can make the characterization change. Meanwhile, the environmental issue that emerges in the stories shows that the power of nature has a great deal in effecting